OC-014 Management of low-grade dysplasia in ulcerative colitis in the uk national health service: the cost-effectiveness of immediate surgery versus ongoing surveillance. (22nd June 2015) - Parker, B; Buchanan, J; Wordsworth, S; East, J; Keshav, S; George, B
Abstract : Introduction: Ongoing surveillance is a potential treatment strategy in the UK National Health Service (NHS) for ulcerative colitis patients who are diagnosed with low-grade dysplasia (LGD) of the flat mucosa, with no associated endoscopically visible lesion. However, given the increased cancer risk following a finding of flat LGD, the costs associated with long-term surveillance and the likely eventual need for surgery, immediate proctocolectomy for flat LGD may both improve health outcomes and also save healthcare costs. The aim of this study was to establish the cost-effectiveness of ongoing surveillance versus immediate surgery for this patient group in the UK NHS. Method: Economic modelling was used to address this decision problem. A Markov model was constructed in which cohort analysis was used to evaluate costs and health outcomes for patients aged from 25–75 years with none, one or two comorbidities affecting surgical risk. Two outcome measures were used: life years and quality adjusted life years (QALYs). The model reflected current UK clinical practice, considered a timeframe of 20 years and adopted a health service perspective. Incremental cost-effectiveness ratios for surveillance versus surgery were calculated. One-way sensitivity analysis was used to establish the key model parameters, while probabilistic sensitivity analysis and cost-effectiveness acceptability curves were used to quantify the overall decision uncertainty. Results: Ongoing surveillance was cost-effective at a threshold of £30, 000/QALY gained at age 62 in the presence of no comorbidities, age 60 in the presence of one comorbidity and at age 51 in the presence of two comorbidities. These results are sensitive to both the colorectal cancer incidence rate for patients under surveillance and to the quality of life in remission post-surgery. There is, however, uncertainty around the results in some age groups: the probability of surveillance being cost-effective is 56.6% at age 65 in the presence of neither of the comorbidities considered (Table 1 ). Conclusion: This study represents the first economic evaluation of surveillance versus surgery in this patient population. As such, this study adds clarity to a decision around which best practice is currently uncertain, and clearly demonstrates which factors are most important for decision-making in this area. Ongoing surveillance may be a cost-effective strategy in this patient population, but only in specific patient subgroups (older patients with multiple comorbidities). In younger patients with fewer comorbidities, surgery likely saves healthcare costs and improves health outcomes. Disclosure of interest: None Declared.